Spirituality in diversity South East Asia meets South Africa - Towards a global view of Spiritual Counselling - Elsdoerfer Ph.D., Dr. Ulrike (AOSIS, 2019)
The purpose of this book is to introduce the special phenomenon of Spiritual Counselling, as it is practised by Christians in South East Asian countries in the last 50 years. Reference is also made to the current theory and practice of Spiritual Care and Counselling, especially as a practice of Christian churches in different countries, predominantly in Indonesia. Previously, it was noticed that there was a lack of knowledge on the above-mentioned field, at least in the European context, but also globally. The author is part of an academic exchange on the subject of Spiritual Counselling between the two regions described: Indonesia (India and Japan attached) and South Africa. The latter is looked at with special regard to Spiritual and/or Pastoral Counselling. The theological frame of reference is Public Theology. It lays foundations, explores and designs the social implications of religious work, especially in multi-religious societies. The book does not aim at giving a perfect survey of the current state of research in the field. It is based on encounters with colleagues, interviews and documents.